A divergence-dependent transmission model for wearable antenna communication in medical application. (April 2021) - Alqahtani, Fayez; Al-Maitah, Mohammed; Said, Wael
Highlights: This paper introduces DDTS method for improving the output of the delivering signals. The convergence free channels are identified based on recurrent feedback analysis. Channel feedback from the state of transmission is analyzed for distortion and noise. Distortion less non-overlapping channel is selected for transmitting sensed signals. Abstract: Wearable sensor technology in medical systems has led to the design and fabrication of body-worn tiny sensing devices. These devices are capable of sensing and transmitting the physiological vitals for clinical analysis and diagnosis. The perplexing factor in transmitting the signals is the occurrence of noise and distortion in the channel. This article introduces a Divergence-Dependent Transmission Scheme to improve the output of the delivering signals. In this transmission scheme, the convergence-free channels are identified based on recurrent feedback analysis. The channel feedback from the previous state of transmission is obtained and is analyzed for distortion and noise. A distortion-less non-overlapping channel is selected for transmitting the sensed signals. The noise mitigation is performed through diagonal analysis of the assessed feedback. This helps to improve the communication efficiency and reduce the noise rate and distortion ratio.